Les variations saisonnières des anomalies spermatiques de bouc de race ARBIA dans la région de Tiaret - RADJA, DJAMAIA SABIHA (My University, 2018)
Our study aims at studying the variations oF abnormal spermatozoa in local breed bucks on one hand. This experiment was carried on a total of 03 bucks and 01female goats at the Veterinary Institute of Tiaret from JUIN2016 till jullay 2017. The semen was collected three times a week with the aid of an artificial vagina (Saturday, Monday and Wednesday). When the artificial vagina was prepared, the bucks were introduced one by one to the collection room to be in contact with an oestrogenised and tied female goat.the tubeofhrvest east at onle put in a barie beth heated at 37c transported to the laboratory to perform a spermocytogram then preparation blades of eosin-negrosin and observation by optical microscope. The seasonal of abnormal spermatozoa varied also from one season to another. The seasonal abnormal spermatozoa mean was the highest during autumn and the lowest during spring. It was 15,97±9,17٪,15,97±9,17٪,25,18±14,92٪,10,35±13,49٪,in Autumn, Winter, Spring and Summer respectively. In conclusion, Arabia bucks of Algeria displayed a clear seasonality of abnormal spermatozoa with very and high levels in winter and spring and low high levels in summer and autumn .
Keywords: anomalie spermatique; bouc; race locale; saisonnalité; Arabia bucks; abnormal spermatozoa; season .